A critical review of the United States regulatory pathways for determining the equivalence of efficacy between CT-P13 and original infliximab (Remicade®) - Kim S; Kim S; Lee H (Dove Medical Press, 2020)
Soohyun Kim, 1, 2,* Siun Kim, 1, 2,* Howard Lee 1– 4 1Department of Transdisciplinary Studies, Graduate School of Convergence Science and Technology, Seoul National University, Seoul, Korea; 2Center for Convergence Approaches in Drug Development, Graduate School of Convergence Science and Technology, Seoul National University, Seoul, Korea; 3Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Korea; 4Department of Molecular Medicine and Biopharmaceutical Sciences, Graduate School of Convergence Science and Technology, Seoul National University, Seoul, Korea*These authors contributed equally to this workCorrespondence: Howard LeeDepartment of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 103 Daehak-Ro, Jongno-Gu, Seoul 110-799, KoreaTel +82 2-740-7602Fax +82 31-888-9575Email howardlee@snu.ac.krAbstract: We evaluated the appropriateness of various equivalence margins for CT-P13, an infliximab biosimilar, in the PLANETRA clinical trial. The 95– 95% method was used to independently determine an equivalence margin by pooling the historical clinical trials with original infliximab versus placebo, identified in a systematic literature search. The constancy assumption with the PLANETRA trial was assessed for each identified historical clinical trial to decide which study was scientifically justifiable to be pooled. A sensitivity analysis was performed for each study-pooling scenario. As a result, we identified two historical clinical trials that were deemed appropriate, whereas the PLANETRA trial pooled three additional studies to determine an equivalence margin, which was accepted by the United States Food and Drug Administration. However, those extra clinical trials did not meet the constancy assumption in baseline characteristics, methotrexate dose, and efficacy assessment time. The clinically more appropriate equivalence margin was 5.7 percentage points, which was much narrower than the 12 percentage points applied in the approval of CT-P13. In conclusion, the equivalence claim for CT-P13 to original infliximab in patients with rheumatoid arthritis did not appear to be supported when the constancy assumption was strictly assessed. The equivalence margin for biosimilars could be determined more conservatively.Keywords: biosimilar, equivalence margin, rheumatoid arthritis, infliximab, CT-P13